Pengaruh Model Scaffolding PjBL dan Self-Efficacy terhadap Penanaman Nilai Tawazun dalam Pembelajaran Ilmu Nahwu di Madrasah Aliyah: Penelitian - A’ffatin Fakhriyah; Imam Nur Aziz (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to examine the influence of the Scaffolding Project-Based Learning (PjBL) model and self-efficacy on the internalization of tawazun (balance) values in Nahwu learning at Madrasah Aliyah. Tawazun, representing the balance in life, was integrated through understanding Arabic sentence structures such as the relationship between mubtada’-khobar and fi’il-fa’il. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The subjects were tenth-grade students of MA Mambaus Sholihin Gresik, selected through purposive sampling. Research instruments included a self-efficacy questionnaire and a tawazun value questionnaire. Data were analyzed using MANOVA tests. The results showed that the application of the Scaffolding PjBL model significantly improved students' understanding of Arabic sentence structure and increased their awareness of balance values in everyday life. Moreover, students’ self-efficacy contributed positively to strengthening the impact of the learning model on the internalization of those values. These findings recommend the use of contextual and reflective learning models to enhance student character development through Arabic language education.